Inverted Shifted Gompertz Distribution with Theory and Applications - Chaudhary, Arun Kumar; Sapkota, Laxmi Prasad; Kumar, Vijay (Pravaha, 2020)
In this work, a novel distribution called an inverted shifted Gompertz distribution by the inverse transformation method is introduced and studied. Some relevant characteristics of inverted shifted Gompertz distribution are mathematically and statistically discussed. To estimate parameters of an inverted shifted Gompertz distribution, some well-known estimation methods, namely LSE, MLE and CVME are used. R software is applied for computational purposes. The applicability of the proposed model has been illustrated considering a real set of data and investigated the goodness-of-fit attained by the inverted shifted Gompertz model through various test statistics and graphical methods. We found that the proposed novel distribution is more flexible and delivered a better fit in contrast with some other selected lifespan models.